1999
DOI: 10.1046/j.1440-1673.1999.00642.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiomyomatosis: Radiological and measured lung function deterioration after contrast‐enhanced computed tomography

Abstract: Pulmonary lymphangiomyomatosis (LAM) is a rare disease of unknown aetiology which occurs exclusively in women, usually of reproductive age. The findings on CT and high-resolution CT (HRCT) are well described and characteristic, and in a young woman they are virtually pathognomonic. A case of symptomatic, radiological and measured lung function deterioration following contrast-enhanced CT in a patient with LAM are reported here. These observations, to the authors' knowledge, have never been reported before. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…The problem of increased extracellular fluid can be compounded by impaired lymphatic drainage. 7 Our patient's hypervolemia during and after surgery probably caused her pulmonary edema; therefore, the likelihood of hypervolemia and pulmonary edema should be borne in mind perioperatively in such patients.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The problem of increased extracellular fluid can be compounded by impaired lymphatic drainage. 7 Our patient's hypervolemia during and after surgery probably caused her pulmonary edema; therefore, the likelihood of hypervolemia and pulmonary edema should be borne in mind perioperatively in such patients.…”
Section: Discussionmentioning
confidence: 82%
“…Teo et al 7 reported that the proliferation of smooth muscle around the veins causes venular congestion in LAM, and the resulting hypervolemia may lead to greater leakage of fluid into the lung parenchyma. The problem of increased extracellular fluid can be compounded by impaired lymphatic drainage.…”
Section: Discussionmentioning
confidence: 99%